2021
DOI: 10.33024/minh.v3i2.3634
|View full text |Cite
|
Sign up to set email alerts
|

Cultural competency and nursing care among sundanese nurses ethnic group in Indonesia

Abstract: Background: Nurses as one of the health professionals who are expecting to have competence in providing nursing care to patients based on cultural background.Purpose: To describe the cultural competency and nursing care among sundanese nurses' ethnic group in Indonesia..Method: A descriptive design with a quantitative approach. The sampling technique in this study used Cluster Random Sampling with the sample of 63 respondents. The instrument used the NCCS (Nurse Cultural Competence Scale). This research conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
1
5
1
Order By: Relevance
“…In this study, the cultural competence subscale with the highest score was cultural awareness, a trend consistent with ndings from the USA [8] , Austria [10] , Taiwan [22,26] , Indonesia [24] , and Assossa in western Ethiopia [15] . However, cultural knowledge emerged as the subscale with the lowest score, mirroring a study conducted in Taiwan [22] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the cultural competence subscale with the highest score was cultural awareness, a trend consistent with ndings from the USA [8] , Austria [10] , Taiwan [22,26] , Indonesia [24] , and Assossa in western Ethiopia [15] . However, cultural knowledge emerged as the subscale with the lowest score, mirroring a study conducted in Taiwan [22] .…”
Section: Discussionsupporting
confidence: 89%
“…However, the current study nding is higher than studies conducted in Indonesia [24] , South Africa [25] , and southwest Ethiopia (1.95 ± 0.32 SD) [13] . The differences in ndings could potentially be attributed to variations in the levels of hospitals among the aforementioned studies.…”
Section: Discussioncontrasting
confidence: 85%
“…6 A cross-sectional study conducted on Sudanese nurses revealed that about 58.7% of the participants had low cultural competency scores. 7 A study conducted in Ethiopia among 270 nurses showed that only 57.3% had good cultural competency nursing care. 8 Health-related errors such as unintended act (omission of plans, miscommunication), or one that does not achieve its intended outcome, failure to plan action to be completed as intended, use of wrong plan to achieve the goal, or deviation from the action of the care that may harm care the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Fully the treatments carried out have an unfavorable health impact on the mother and her baby. This requires special attention to overcome (Pitriani et al, 2021) The culture of the Batak Toba tribe has its own culture in living life. Culture influences all behaviors passed down from generation to generation.…”
Section: Resultsmentioning
confidence: 99%